Detection of metabolic disorders in high-risk patients: a pilot study in Salvador, Bahia Detecção de doenças metabólicas em pacientes de alto-risco: estudo piloto em Salvador, Bahia - Maria Betânia Pereira; Gildásio Carvalho da Conceição; Janice C. Coelho; Moacir Wajner; Roberto Giugliani (Arquivos de Neuro-Psiquiatria)
The purpose of this pilot-study was to evaluate the applicability of a screening protocol for the detection of inborn errors of metabolism (IEM) in high-risk patients. The protocol was applied in 65 patients referred to the Medical Genetics Laboratory of the University Hospital Professor Edgard Santos due to the suspicion of an IEM. Eight of these patients (12.3%) displayed an abnormal result in the screening protocol. These patients, along with 22 who displayed normal results in the screening protocol but who presented clinical symptoms or signs suggestive of an IEM not detectable by the tests applied, were selected for a further diagnostic investigation. In 5 of these 30 patients (7.7% of the total sample) it was possible to establish the diagnosis of an specific IEM. The results indicate that the designed screening protocol was sucessfully applied, allowing the detection of affected patients in a frequency comparable to that observed in larger studies performed elsewhere. The continuation of this study and the enlargement of the sample will help to delineate the profile of IEM in northeast of Brazil and will allow the identification of a significative number of patients and families, who could benefit from the therapeutic and preventive measures available for these diseases. O objetivo deste estudo-piloto foi avaliar a aplicabilidade de protocolo dc triagem para a detecção de erros inatos do metabolismo (EIM) em pacientes de alto risco. O protocolo foi utilizado em 65 pacientes encaminhados ao Laboratório de Genética Médica do Hospital Universitário Prof. Edgard Santos por suspeita de apresentar um EIM. Oito desses pacientes (12,3%) apresentaram resultado anormal no protocolo de triagem. Estes, junto com outros 22, cujo protocolo de triagem teve resultados normais mas que apresentavam sinais ou sintomas clínicos sugestivos de um EIM que poderia passar desapercebido pelos testes realizados, foram selecionados para investigação diagnostica adicional. Em 5 desses 30 pacientes (7,7% da amostra total) foi detectado um EIM. Estes resultados indicam que o protocolo de triagem planejado foi aplicado com sucesso, permitindo a detecção de pacientes afetados em uma frequência comparável à observada em estudos mais amplos realizados em outros locais. A continuação do estudo e a ampliação da amostra vão ajudar a delinear- o perfil dos EIM no nordeste brasileiro, bem como a identificação de número significativo de pacientes e de famílias com EIM, que podem se beneficiar das medidas preventivas e terapêuticas disponíveis para essas doenças.